ANALISA KEBUTUHAN MATERIAL DAN BIAYA COATING PADA REPARASI LAMBUNG KAPAL NELAYAN BERBAHAN KAYU UKURAN DI BAWAH 5GT - Ainur Rofiq; Yulia Ayu Nastiti; Sofianna Agustin (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
This research contains the coating repair process and costs required for a fishing boat with a hull length of 11 meters, starting from docking and cleaning old paint, with the aim of finding out the amount of materials neededand coating costs needed for a wooden boat. To determine how much paint should be used for wooden ship repairs. Qualitative description method, which is included in the qualitative research category. This writer aims to reveal events, phenomena, variables, situations and circumstances, facts that occur. Because almost all ship building materials are wood. In order for paint to meet the specified requirements, it must comply with the specified painting process, pre-inspection, surface preparation, paint preparation, and paint application. For thisreason, it is necessary to know the various types of painting techniques that must be prepared before carrying outthe process of painting the ship's hull. The coating process on the ship's hull uses 2 different types of paint, namely the Avian brand for base paint and the Avian moustrial and marine coating brand for color paint. Where each part of the ship is covered with 2 parts. i.e. base paint, the result is 10 liters with a hull area of 48m2. With a totalcost of Rp740,000, the yield of color paint was 9.6 liters, namely Rp816,000. So from this research it can be concluded that using base paint and anti-fouling paint is more profitable because it has been calculated and you can buy the right paint without having to have any leftovers. And the usage time is longer because the paint thickness is according to the specified one.